Therapeutic treatment of hepatitis E virus infection in pigs with a neutralizing monoclonal antibody - Isabella Hrabal; Elmira Aliabadi; Sven Reiche; Saskia Weber; Cora M. Holicki; Laura Schmid; Christine Fast; Charlotte Schröder; Benjamin Gutjahr; Patrick Behrendt; Martin H. Groschup; Martin Eiden (Scientific Reports)
Abstract Hepatitis E virus (HEV) poses a significant risk to human health. In Europe, the majority of HEV infection are caused by the zoonotic genotype 3 (HEV-3), which can cause chronic hepatitis E in immunocompromised patients and those with pre-existing liver disease, and may eventually develop into fatal liver cirrhosis. In this study, we examined the effectiveness of a monoclonal antibody (MAb) treatment strategy using a well established HEV-3 pig model with intravenous infection. For this purpose, nine MAbs raised against the viral capsid protein were generated and the neutralizing activities were compared using in vitro assays. The antibody with the highest neutralizing activity, MAb 5F6A1, was selected for an in vivo study in pigs infected with HEV-3. Following the initial infection of pigs with HEV-3, MAb 5F6A1 was administered intravenously one and seven days post-infection. The results suggest MAb 5F6A1 significantly reduced viremia and virus shedding in pigs infected with HEV-3. This study provides significant insight into the dynamics of HEV infection in pigs and highlights the efficacy of MAb based therapy as an option for treating HEV in porcine hosts and, potentially, humans.